Being “in” or “out” of the game: subjective and acoustic reactions to exclusion and popularity in social anxiety - Gilboa-Schechtman, Eva; Galili, Lior; Sahar, Yair; Amir, Ofer (Frontiers in Human Neuroscience, 2014)
Social Anxiety (SA) has been shown to be associated with compensatory deficits in pro-social behavior following exclusion and with failure to capitalize on social success. We assessed the subjective and expressive responses of high (n=48) and low (n=56) socially anxious individuals to exclusion, acceptance, and popularity induced by a participation in an online ball-tossing task. Before the manipulation, participants read aloud neutral and command utterances. Following the manipulation, participants rated their mood and cognitions and re-read the utterances. Acoustic properties (fundamental frequency–mF0, intensity, speaking rate) of these utterances were analyzed. We found greater differences in self-esteem between high and low socially anxious individuals following the exclusion condition, as compared to the acceptance condition. Among low socially anxious individuals, exclusion promoted increased vocal confidence, as indicated by decreased mF0 and increased vocal intensity in uttering commands; High socially anxious individuals exhibited an opposite reaction, responding to exclusion by decreased vocal confidence. Following popularity, high SA was associated with decreased enhancement in mood and self-esteem in women but not in men. Consistent with evolutionary and interpersonal accounts of SA, we highlight the importance of examining the effects of SA and gender on events indicating unambiguous and unanimous social acceptance. Examining reactivity to changes in belongingness may have important implications for understanding the core mechanisms of SA.